The community capacity curve applied to reforestation: a framework to support success. (2nd January 2023) - Herbohn, John; Ota, Liz; Gregorio, Nestor; Chazdon, Robin; Fisher, Robert; Baynes, Jack; Applegate, Grahame; Page, Tony; Carias, Dora; Romero, Claudia; Putz, Francis E.; Firn, Jennifer
Abstract : Community involvement is critical for the success of many interventions designed to promote reforestation. To secure this involvement, it helps to recognize that communities are heterogenous both within and among themselves and possess diverse mixes of livelihood assets required to implement reforestation. We explore the relationship between livelihood assets and reforestation success and outline a conceptual model that we call the community capacity curve (CCC) applied to reforestation. We argue that the shape of the CCC is sigmoidal. Importantly, communities at the lower end of the CCC have limited capacity to implement reforestation projects without substantial and ongoing capacity building and other sorts of support, including through livelihood projects that improve food security and provide cash benefits. Communities at the higher part of the CCC have greater capacity to implement reforestation projects, especially projects focused on biodiversity and environmental services. The CCC can help design, implement, monitor and assess reforestation projects, select appropriate livelihood activities and types of reforestation, select communities suited to a reforestation project, guide implementation and understand projects' successes and failure. The CCC also provides a framework to engage with policy makers and funding bodies to explore the types of support for communities to reforest successfully. This article is part of the theme issue 'Understanding forest landscape restoration: reinforcing scientific foundations for the UN Decade on Ecosystem Restoration'.